Social innovation in health and community-driven engagement as a key strategy for addressing COVID-19 crisis challenges: insights and reflections from the multicultural society of Iran - Khazaee-Pool, Maryam; Pashaei, Tahereh; Ponnet, Koen (Frontiers in Public Health, 2023)
Background: One of the running strategies to appeal social cooperation and engagement to offer operative, quick, and organized interventions in crises is via social innovation (SI). In this regard, community engagement (CE) also is an operative and innovative community health approach for successful health consequences. There is restricted available awareness regarding SI strategies to CE in confirming practical feedbacks to the COVID-19 crisis challenges. In this document, we contribute to bridging this gap by emphasizing the experience of social innovative strategies based on community-driven engagement in Iran. Methods This qualitative study was conducted in seven provinces of Iran, including Mazandaran, Zanjan, Golestan, Lorestan, Tehran, Kurdistan, and Khuzestan in the period from September 4, 2021, to March 1, 2022. A sample of Iranian people (15–71 years) was selected by purposeful and snowball sampling methods to participate in 187 semi-structured telephone interviews. Participants were recruited from three levels of the community, including community leaders, healthcare providers, and laypeople. The data collection tool was an interview guide, which was designed based on literature reviews. Data were analyzed by conventional content analysis. Exploratory analyses were performed to find social innovative strategies based on community engagement used during the COVID-19 crisis in Iran. The interviews continued until data saturation was reached. Results After analyzing the results, we distilled innovative strategies into six main themes and 37 categories: (1) information giving/sharing, (2)consultation, (3)involvement/collaboration, (4) health education and prevention, (5) empowering, and (6) advocacy. The results disclosed that participants were very driven to engage in the management and control of the COVID-19 crisis, even though it met large challenges. Conclusions The results specified that information giving/sharing, consultation, involvement/collaboration, health education, prevention, empowerment, and advocacy are the most innovative strategies that might encourage and engage the community to participate in the COVID-19 crisis prevention and control.